STUDIES ON HYDRODYNAMIC TORQUE ON GUIDE VANES OF FRANCIS TURBINES UNDER STEADY STATE OPERATION - Menezes, Pedro Henrique Bastos (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
According to the Brazilian National Electric Energy Agency (ANEEL), over 60% of electricity produced in Brazil comes from hydraulic resources. Most turbines in Brazilian hydroelectric power plants are Francis type, in which the flow is controlled by rotating guide vanes. Any resistive hydraulic torque on these vanes are overcome by servo motors. The estimation of resulting torque was performed by Computational Fluid Dynamics (CFD), using techniques to simulate the flow from the vanes to the exit of the draft tube. The geometries and experimental data were collected for free on Francis-99 website, held by the Norwegian University of Science and Technology (NTNU). Based on the axi-periodic geometry, the flow was divided into channels. One of them was divided into three isolated tracks with independent fluid meshes and suitable boundary conditions, considering steady state operation. In order to realise the simulation, the softwares OpenFOAM and ParaView were used. Computational techniques as Mixing Plane, General Grid Interface and Multiple Rotating Frames of Reference were applied to make the interfaces between sections and to emulate effects of rotation.The pressure field on the surface of a guide vane was then integrated with respect to area so that the resulting hydraulic torque was found.